2022
DOI: 10.3390/plants11091129
|View full text |Cite
|
Sign up to set email alerts
|

Bergenia pacumbis (Buch.-Ham. ex D.Don) C.Y.Wu & J.T.Pan: A Comprehensive Review on Traditional Uses, Phytochemistry and Pharmacology

Abstract: The influence of medicinal plants on humanity spans time immemorial. These plants are also used at present with local and tribal peoples for the cures of various illnesses. Nature has produced an immense number of medicinal plants, which directly or indirectly help to treat various ailments and have numerous applications in the fields of pharmaceuticals, agriculture, food flavors and preservatives, aromas, and cosmetics. Bergenia pacumbis (Buch.-Ham. ex D.Don) C.Y.Wu & J.T.Pan (synonym: Bergenia ligulate E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A huge recovery in the interest and use of medicinal plants has been witnessed in the previous decade. For a considerably long time, the plants belonging to the genus Bergenia have received notable attention for their restorative properties against ailments and have been broadly utilized in traditional medicines in various regions, particularly in the Asian continent, including India, Pakistan and Nepal [ 20 ]. Rhizomes of the species belonging to the genus Bergenia have been used in folk medicine for their antiscorbutic, astringent, diuretic, antipyretic, and ophthalmic properties [ 21 ].…”
Section: Bergenia Ligulata As Traditional Herbal Medicinementioning
confidence: 99%
“…A huge recovery in the interest and use of medicinal plants has been witnessed in the previous decade. For a considerably long time, the plants belonging to the genus Bergenia have received notable attention for their restorative properties against ailments and have been broadly utilized in traditional medicines in various regions, particularly in the Asian continent, including India, Pakistan and Nepal [ 20 ]. Rhizomes of the species belonging to the genus Bergenia have been used in folk medicine for their antiscorbutic, astringent, diuretic, antipyretic, and ophthalmic properties [ 21 ].…”
Section: Bergenia Ligulata As Traditional Herbal Medicinementioning
confidence: 99%
“…At present, approximately 152 volatile and non-volatile compounds are isolated from Bergenia genus which contained a wide range of bioactive compounds of therapeutic value [3]. The phytochemical analysis showed that the plant extract is a rich source of secondary metabolites such as alkaloids, coumarins, phenol, flavonoids, benzenoids, tannin, saponins, lactones and terpenoids which make this plant a valuable medicinal herb with broad spectrum pharmacological activities like antioxidant, antiviral, antibacterial, diuretic, antipyretic, anti-inflammatory, antioxaluria and antidiabetic activities [3,4]. Wild medicinal plants are harvested as a raw material for medicine, which is the main cause of genetic diversity loss and degradation of habitat.…”
Section: Introductionmentioning
confidence: 99%
“…The plant grows up to a height of 30-35 cm and has a rhizomatous rootstock and glabrous leathery leaves that form a rosette. It flowers between April and June with white to pink petals [25]. The genus Bergenia comprises 32 species that are mainly distributed in Asia [26].…”
Section: Introductionmentioning
confidence: 99%